Presence of microcalcification in the arterial wall and its relationship to the maturation of the arteriovenous fistula in patients with chronic kidney disease stage 4 and 5 - Jun, Tang Weng (2018)
Introduction: A functioning and reliable arteriovenous fistula is a lifeline for individuals suffering from chronic kidney disease who require regular haemodialysis treatment. The success and failure to arteriovenous maturation have been frequently related to patient and surgeon factors. The goal of this study is to evaluate the impact of pre-existing artery wall abnormality on arteriovenous outcome. Specifically, to assess the association between the formation of microcalcification in the intima-media of the arterial wall and arteriovenous fistula maturation. Method: 138 participants with stage IV and V chronic kidney disease were included in this prospective observational study. Preoperative vascular mapping using an ultrasound was performed by the operating surgeon to evaluate the condition and size of the vessels to fulfil the inclusion criteria. Intraoperatively, the vessel size was measured again prior to anastomosis under magnified view. A specimen from the arterial wall of 3-4 mm in diameter was obtained from the arterotomy for histopathology assessment. Specimens were stained with Hematoxylin and Eosin, Verhoeff’s Van Gieson and Von Kossa stains. A pathologist who was oblivious to the patients′ clinical information, examined the specimen for microcalcification in the intimamedia of the arterial wall and the media thickness. Arteriovenous maturation was assessed at 6 weeks, post-operatively, with the guidance of a duplex ultrasound. Results: From the total of 138 participants, 110 participants (79.7%) had matured arteriovenous fistula in 6 weeks. The mean size of the artery measured intraoperatively was 3.82 ± 1.33 mm and the vein was 4.05 ± 1.20 mm. Microcalcification in the arterial tunica media which was hypothesised to be the cause of the arteriovenous fistula failure was insignificant, with a P-value of 0.115. Despite having atherosclerosis in the artery, 83.3% of the arteriovenous fistula matured. Conclusion: Microcalcification and atherosclerosis are frequently seen in the arteries of chronic kidney disease patients, but they do not explain arteriovenous fistula non-maturation.